2018
DOI: 10.1007/s12519-018-0128-8
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric appendicitis with appendicolith often presents with prolonged abdominal pain and a high risk of perforation

Abstract: Pediatric appendicitis with appendicolith often presents with prolonged abdominal pain and severe clinical conditions with a high risk of perforation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 28 publications
3
23
1
2
Order By: Relevance
“…The presence of an appendicolith has been identified as an independent prognostic risk factor for treatment failure in nonoperative treatment of uncomplicated acute appendicitis [13,14], and it has also been shown to be associated with appendiceal perforation [15][16][17]. In the randomized study of Vons et al [7] comparing antibiotic treatment with appendectomy in patients with computed tomography (CT)-verified uncomplicated appendicitis, patients presenting with an appendicolith were randomized and the presence of an appendicolith was associated with antibiotic treatment failure.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of an appendicolith has been identified as an independent prognostic risk factor for treatment failure in nonoperative treatment of uncomplicated acute appendicitis [13,14], and it has also been shown to be associated with appendiceal perforation [15][16][17]. In the randomized study of Vons et al [7] comparing antibiotic treatment with appendectomy in patients with computed tomography (CT)-verified uncomplicated appendicitis, patients presenting with an appendicolith were randomized and the presence of an appendicolith was associated with antibiotic treatment failure.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported the prevalence of appendicolith in pediatric appendicitis has reached at 50 %. 12 Distinctive differences in the incidence rate of pediatric appendicitis with appendicolith may be due to diverse study population. Additionally, we just included patients diagnosed during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…16 Larger size fecalith located at the base of appendix was associated with complicated appendicitis. 12 It may be reasonable to presume that the emergence of appendicolith could be a high risk factor of appendicitis. On the other hand, appendicoliths detected by CT scan without inflammatory signs may be transient without special clinical importance.…”
Section: Discussionmentioning
confidence: 99%
“…En estudios previos, se informó que la prevalencia de apendicolito en la apendicitis pediátrica alcanzó el 50 %. 12 Las diferencias características en la tasa de incidencia de apendicitis con apendicolito en la niñez podrían deberse a las variaciones en la población del estudio. Además, en nuestro estudio, se incluyeron solo pacientes diagnosticados durante la cirugía.…”
Section: Discussionunclassified
“…16 Un fecalito más grande en la base del apéndice se asoció con apendicitis complicada. 12 Podría ser razonable suponer que la aparición de apendicolito podría ser un factor de riesgo de apendicitis elevado. Por el otro lado, el apendicolito detectado por TC sin signos inflamatorios podría ser transitorio y carecer de relevancia clínica particular.…”
Section: Discussionunclassified